Biology of Omaspides pallidipennis Boheman, 1854 (Coleoptera: Chrysomelidae: Cassidinae) - Paula A. A. Gomes; Fábio Prezoto; Fernando A. Frieiro-Costa (Psyche: A Journal of Entomology, 2012)
The biology and the feeding habits of the subsocial species Omaspides pallidipennis were studied at the Floresta Nacional de Passa Quatro, MG, Brazil, during the period from October 2010 to April 2011. The species was bivoltine, beginning its reproductive and food cycle in October (spring) and seeking its diapause sites in April (autumn). The juveniles took 54.4 days on average to complete their development, a period in which the female remained close to offspring, only feeding during the larval stage of the juveniles. It is a monophagous species, feeding only on Ipomoea alba Linnaeus (Convolvulaceae). In the first cycle, the average number of eggs was 55.7±15.5 eggs per egg cluster (n=1,837 eggs in 33 clusters) and in the second it was 61.6±14.2 eggs per egg cluster (n=5,607 eggs in 91 clusters). Oviposition peaks were observed in the months of November and February. The average durations of the incubation period and the larval and the pupal development in the first cycle were 19.2±1.4; 26.0±1.5; 8.7±0.8 days, respectively. In the second cycle they wrere 16.7±1.4; 27.0±2.4; 10.2±1.5 days, respectively.